Hubungan Pengetahuan, Sikap dan Dukungan Suami dengan Pemanfaatan Layanan Antenatal Care di Wilayah Kerja Poskesdes Compong Kabupaten Sidenreng Rappang - Suarmi S.; Mardhatillah Mardhatillah; Khaeriyah Adri (Pusat riset dan Inovasi Nasional, 2025)
Antenatal Care (ANC) is an essential component of maternal health services that plays a vital role in maintaining the health of the mother and fetus during pregnancy and delivery. In Indonesia, coverage of ANC services K1 has reached 100%, but coverage of K4 has only reached 78% and has not met the national target. A case study in Sidenreng Rappang Regency showed better results with K1 coverage of 98% and K4 reaching 97%, although there is still room for improvement. This quantitative study with a cross-sectional design aims to analyze the relationship between maternal knowledge, attitudes, and husband's support factors on the utilization of ANC services at the Compong Village Health Post. The study population included 190 mothers with toddlers registered at the Compong Village Health Post. Sampling was carried out using the Slovin formula with a 95% confidence level and a 5% margin of error, resulting in 127 respondents as the research sample. The data collection method was carried out through a structured questionnaire containing questions about respondent characteristics, level of knowledge, attitudes towards ANC, and level of husband's support. Data analysis used the Chi-Square statistical test with a significance level of p<0.05 to determine the relationship between the independent and dependent variables. The results revealed several important findings. First, there was a significant relationship (p=0.002) between maternal knowledge and utilization of ANC services. Second, maternal attitudes also showed a significant relationship (p=0.001) with the frequency of ANC visits. Third, husband's support was shown to have a significant influence (p=0.003) on maternal participation in ANC programs. These findings confirm the multifactorial role in determining ANC service utilization. Practical implications of this study include recommendations for improving health education programs that not only target pregnant women but also actively involve husbands.